Oral Pathology in the Pediatric Patient A Clinical Guide to the Diagnosis and Treatment of Mucosal and Submucosal Lesions - Philipone, Elizabeth; Yoon, Angela J.; Koutlas, Ioannis G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book, now in an extensively revised second edition, is a practical, user-friendly guide to the clinical diagnosis and treatment of the oral mucosal and intraosseous lesions most frequently encountered in pediatric patients. For each entity, a characteristic clinical photograph is provided, the clinical appearance is concisely described, and guidance is offered on differential diagnosis and treatment options. Oral indications of systemic diseases are addressed in a separate section, and mucosal indicators of drug use, sexual abuse, and eating disorders are also identified. The book includes new chapters on cysts and psuedocysts, odontogenic tumors, non-odontogenic lesions and osseous manifestations of systemic diseases. Oral lesions are a relatively common occurrence in the pediatric population. Fortunately, most of these lesions are transient and can be diagnosed clinically; examples include aphthous ulcers, traumatic ulcers, and lesions of infectious etiology such as viral lesions and candidiasis. There are also a number of mucosal lesions, such as mucoceles and viral papillomas, that require biopsy for diagnosis and/or surgical excision for treatment. This book will assist the practitioner in diagnosing and treating both transient and persistent mucosal lesions. .
Mucosal Lesions: Mucosal Lumps and Bumps with Smooth Surfaces -- Papillary Lesions -- Oral Ulcers -- White and Red Macules and Patches.-Gingival Lesions -- Pigmented Lesions. Mucosal Manifestations of Systemic Disease, Habits, and Abuses: Mucosal Manifestations of Gastrointestinal Disease -- Mucosal Manifestations of Nutritional Deficiencies -- Mucosal Manifestations of Immunosuppression -- Oral Soft Tissue Manifestations of Hematologic Abnormalities and Diseases -- Oral Manifestations of Habits and Abuses. Intraosseous lesions: Cysts and Psuedocysts -- Odontogenic tumors -- Non-Odontogenic Lesions -- Osseous Manifestations of Systemic Diseases.
Keywords: Dentistry; Pediatrics; Dentistry; Pediatrics